Child-to-adult transition: a survey of current practices within the European Reference Network for Rare Neurological Diseases (ERN-RND) - Nanetti, Lorenzo; Kearney, Mary; Boesch, Sylvia; Stovickova, Lucie; Ortigoza-Escobar, Juan Darío; Macaya, Alfons; Gomez-Andres, David; Roze, Emmanuel; Molnar, Maria-Judit; Wolf, Nicole I; Darling, Alejandra; Vasco, Gessica; et al. (Neurological sciences, 2024)
BACKGROUND: Transition from child-centered to adult-centered healthcare is a gradual process that addresses the medical, psychological, and educational needs of young people in the management of their autonomy in making decisions about their health and their future clinical assistance. This transfer is challenging across all chronic diseases but can be particularly arduous in rare neurological conditions. AIM: To describe the current practice on the transition process for young patients in centers participating in the European Reference Network for Rare Neurological Diseases (ERN-RND). METHODS: Members of the ERN-RND working group developed a questionnaire considering child-to-adult transition issues and procedures in current clinical practice. The questionnaire included 20 questions and was sent to members of the health care providers (HCPs) participating in the network. RESULTS: Twenty ERN-RND members (75% adult neurologists; 25% pediatricians; 5% nurses or study coordinators) responded to the survey, representing 10 European countries. Transition usually occurs between 16 and 18 years of age, but 55% of pediatric HCPs continue to care for their patients until they reach 40 years of age or older. In 5/20 ERN-RND centers, a standardized procedure managing transition is currently adopted, whereas in the remaining centers, the transition from youth to adult service is usually assisted by pediatricians as part of their clinical practice. CONCLUSIONS: This survey demonstrated significant variations in clinical practice between different centers within the ERN-RND network. It provided valuable data on existing transition programs and highlighted key challenges in managing transitions for patients with rare neurological disorders.
Keywords: Delivery of Health Care; vzácné nemoci; mladiství; Rare Diseases; průzkumy a dotazníky; dospělí; Nervous System Diseases; nemoci nervového systému; lidé; Adult; dítě; Child; Adolescent; Surveys and Questionnaires; Evropa; poskytování zdravotní péče; Humans; Europe